Relationship between catastrophizing, kinesiophobia, disability and pain intensity in patients with painful shoulder syndrome - Díaz Narváez, Víctor Patricio.; Cornejo Mercurio, Moisés Alejandro.; Artigas Albornoz, Julio Fernando.; Veliz Reyes, Yerko Brian.; Díaz Escobar, Cristian. (Federación Española de Docentes de Educación Física, 2023)
Introduction: Painful shoulder syndrome is considered a relevant public health problem, because of its high prevalence, disease burden, economic cost to the individual and health care system. Objective: To describe the relationship between catastrophizing, kinesiophobia and upper limb functional disability with pain intensity in patients with painful shoulder syndrome. Materials and methods: Quantitative, explanatory, correlational cross-sectional study. The sample consisted of 30 patients (20 women - 10 men) with painful shoulder syndrome attended in a public health center, Santiago de Chile. It was applied: Visual Analog Scale (VAS), Catastrophizing Scale, Tampa Scale for kinesiophobia, Quick DASH for disability and shoulder functionality. Results: The study shows a significant relationship for the variables of catastrophization and pain intensity (Kendall's tau b = 0.496, P = 0.005), for limitation of functionality and pain intensity (Kendall's tau b = 0.365, P = 0.008), with the exception of the relationship between kinesiophobia and pain intensity (Kendall's tau b = 0.181, P = 0.186). Conclusion: The cognitive factor of catastrophizing and functional disability of the shoulder is directly related to the perceived pain intensity in patients with painful shoulder syndrome. The importance of its evaluation for rehabilitation is based on a biopsychosocial and multidisciplinary approach.
Keywords: Kinesiofobia; Hombro; Dolor crónico; Catastrofización